Strategi Guru Sharaf di Pesantren: Dari Metode Klasik hingga Inovatif - Muhammad Fariq Heemal Attruk; Salsabila Ramadhani; Farhan Ardhana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to identify, categorize, and synthesize teacher strategies in teaching sharaf (Arabic morphology) at pesantren through an integrative literature review approach. Literature searches were conducted using Google Scholar, DOAJ, and Scopus, resulting in 22 articles that met the inclusion criteria. The findings reveal three main strategic dimensions: material delivery, practice and reinforcement, and evaluation and feedback. Material delivery strategies include classical methods (sorogan and bandongan), inductive and deductive approaches, and innovative approaches using visual media, singing, and game-based learning. Practice strategies involve drills, memorization, individual submission, collaborative learning, gamification, and contextual projects. Evaluation strategies include kitab kuning-based assessment, formal tests, oral evaluation, and integrated assessment systems. The study concludes that sharaf learning strategies have developed from traditional approaches toward more adaptive and innovative models while maintaining classical methods’ strengths in individual guidance. These findings highlight the need for further empirical studies to develop standardized evaluation systems and optimize the integration of innovative strategies in various pesantren contexts.